Overlapping niches between two co‐occurring invasive fish: the topmouth gudgeon Pseudorasbora parva and the common bleak Alburnus alburnus. Issue 5 (14th September 2020) - Balzani, Paride; Gozlan, Rodolphe E.; Haubrock, Phillip J.
Abstract: Invasive fish species impact aquatic ecosystems and modify native communities, often leading to a decline in local species. These ecological impacts include the transmission of pathogens, predation, competition as well as hybridization. Two invasive fish species, the common bleak Alburnus alburnus and the topmouth gudgeon Pseudorabora parva, have both been recently found co‐occurring in several regions of southern Europe, such as the Italian Arno River. Nonetheless, the trophic relationships among invasive fish species, especially cyprinids, remain poorly understood, and no studies have reported the trophic interaction between these two species. This study compared length–weight relationship and used stomach content and stable isotope analysis of two co‐occurring populations in the Arno River to characterize the growth and overlap of potential trophic niches. It also found similar allometric growth in both species, a wider generalist trophic niche for P. parva and a more specialized niche for A. alburnus . A considerable niche overlap was found, suggesting that feeding competition can occur if resources were to be limited. Moreover, the niche of P. parva was more likely to overlap with that of A. alburnus than vice versa, suggesting that P. parva can be considered as a potential over competitor. Nonetheless, the authors found in the overlapping populations no evidence of realized competition, probably avoided through a combination of fine‐scale mechanisms. They also highlighted that these two invasive species can co‐exist and share resources, at least in an open ecosystem like a river, thus potentially doubling up their trophic impact on local communities.